Coherence of the Rules of Sharia Against Pancasila - Zaidah Nur Rosidah (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This paper aims to find the coherence of sharia principles towards Pancasila. Pancasila as the philosophical basis of the state has an important role in the life of the nation and state. The principles of sharia are important principles for Muslims in muamalah. The type of research used is normative legal research to find coherence between sharia principles in Pancasila. The approach used is a conceptual approach. Secondary data were collected through literature study. Analyze the data using the syllogism method of deduction and interpretation, where the sharia principle is coherent with Pancasila. The results showed that first, the concept of ownership of property and payment of zakat and justice is coherent with the first, second and fifth precepts of Pancasila. Second, the principle of willingness is coherent with the second principle of humanity which is just and civilized, the principle of equality is coherent with the third principle of Indonesian unity, the principle of honesty and truth is coherent with the principle of the Almighty God and the second principle of fair and civilized humanity, the principle of benefit and mutual advantageous in line with the fifth precepts of social justice for all Indonesian people, the written principle in sharia principles is in line or coherent with the fourth principle of populism, which is led by wisdom in deliberation / marriage. Keywords: Coherence; Sharia Principles; Pancasila.